Does financial inclusion promote investment and affect residents' happiness?—Evidence from China - Xu, Qiuyan; Sun, Wu (Frontiers in Psychology, 2022)
With the rapid development of inclusive finance, the popularity of financial services is increasing, and the level of financial literacy of residents has gained. Using data from the 2013, 2015 and 2017 China General Social Surveys (CGSS) and the China Digital Inclusive Finance Development Index to analyze residents' investment behavior in China, this study finds that inclusive finance significantly increased residents' investment participation and decrease their sense of happiness at the same time. This study demonstrates the effectiveness of China's financial inclusion policy and provides ideas for its further improvement.